Arkitectonic a quasi-generative disaster education training facility in preparation for The Big One - Simon, Andrea Monica B.
In light of Metro Manila facing the imminent threat of “The Big One” earthquake, this study aims to address the pressing need for innovative disaster education training. It explores the integration of architectural design, advanced technologies, and gamification concepts in disaster preparedness training to enhance learning and retention, challenging traditional methods, and providing insights into the potential of integrating these methods. Its primary objectives are to review literature on gamification and disaster education, synthesize it, develop principles for design, and apply findings to reimagine disaster education training experiences.